FPGA Implementation of a Robust MPPT of a Photovoltaic System Using a Fuzzy Logic Controller Based on Incremental and Conductance Algorithm - Allani, M. Y.; Mezghani, D.; Tadeo, F.; Mami, A. (Engineering, Technology & Applied Science Research, 2019)
Climate dependence requires robust control of the photovoltaic system. The current paper is divided in two main sections: the first part is dedicated to compare and evaluate the behaviors of three different maximum power point tracking (MPPT) techniques applied to photovoltaic energy systems, which are: incremental and conductance (IC), perturb and observe (P&O) and fuzzy logic controller (FLC) based on incremental and conductance. A model of a photovoltaic generator and DC/DC buck converter with different MPPT techniques is simulated and compared using Matlab/Simulink software. The comparison results show that the fuzzy controller is more effective in terms of response time, power loss and disturbances around the operating point. IC and P&O methods are effective but sensitive to high-frequency noise, less stable and present more oscillations around the PPM. In the second section, the FPGA platform is used to implement the proposed control. The FLC architecture is implemented on an FPGA Spartan 3E using the ISE Design Suite software. Simulation results showed the effectiveness of the proposed fuzzy logic controller.